Leviathan and Woman – Pateman on Hobbes’s Standpoint - Guczalska, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Carole Pateman is well known in several fields of research: the ideas of democracy, the problem of political obligation and criticism of liberalism. Her political theory also belongs to the feminist tradition. In this domain, Pateman posits a mutual dependence between patriarchy and social contract. To substantiate that hypothesis, she analyses and re-evaluates classical political thinking, including the ideas of Thomas Hobbes. The author of Leviathan holds an original standpoint on the question of women and cogently links their social role to the construction of the overall political system. In Pateman’s view, modern patriarchalism can be traced back to Hobbes’ thinking. This article presents an interpretation of how, and in particular Hobbes’s views on women and on how his political theory guarantees the validity and universality of patriarchal law.